2003
DOI: 10.1128/iai.71.8.4472-4486.2003
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Expression of a Polymorphic, Charged Antigen in the Protozoan Parasite Entamoeba histolytica

Abstract: We have identified a novel stress inducible gene, Ehssp1 in Entamoeba histolytica, the causative agent of amebiasis. Ehssp1 belongs to a polymorphic, multigene family and is present on multiple chromosomes. No homologue of this gene was found in the NCBI database. Sequence alignment of the multiple copies, and genomic PCR data restricted the polymorphism to the central region of the gene. This region contains a polypurine stretch that encodes a domain rich in acidic and basic amino acids. Under normal culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Genes encoding stress-related proteins were among the most highly expressed ones. Noteworthy findings included the ninefold overexpression of the ssp1 stress-inducible gene (Satish et al, 2003), peroxiredoxin (providing protection from oxidative stress) and, very close to scores, two isoforms of Hsp90 (an important chaperone in the stress response). Genes involved in the ubiquitin-dependent proteolysis pathway and those encoding 26S proteasome regulatory complex components were also upregulated in virulent parasites.…”
Section: Resultsmentioning
confidence: 94%
“…Genes encoding stress-related proteins were among the most highly expressed ones. Noteworthy findings included the ninefold overexpression of the ssp1 stress-inducible gene (Satish et al, 2003), peroxiredoxin (providing protection from oxidative stress) and, very close to scores, two isoforms of Hsp90 (an important chaperone in the stress response). Genes involved in the ubiquitin-dependent proteolysis pathway and those encoding 26S proteasome regulatory complex components were also upregulated in virulent parasites.…”
Section: Resultsmentioning
confidence: 94%
“…The majority (ϳ80%) of genes in this category did not have highly conserved homologues in the E. dispar SAW760 database, and none of the genes had been identified in previous studies relating to amebic virulence. Interestingly, five of the identified genes (147.m00110, 543.m00021, 864.m00008, 296.m00047, and 460.m00024) showed homology to the open reading frame found in the SSE58 repeat region identified as encoding a stress-dependent polymorphic charged antigen (Ehssp1) (48). We confirmed a lack of expression in E. dispar SAW760 and E. histolytica Rahman for one gene family member (460.m00024) by Northern blot analysis (data not shown; P. Vanchinathan, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of genes that contain ⩾2 of these motifs are annotated as hypothetical proteins by The Institute for Genomic Research, but a number of those have significant BLASTP matches to a polymorphic, charged antigen, E. histolytica stress-sensitive protein 1 (Ehssp1) (32). Three subfamilies of the Ehssp gene family were previously identified, varying in domain composition, primarily of the charged medial domain (32). We created an HMM of the C-terminal domain shared by all three subfamilies.…”
Section: Resultsmentioning
confidence: 99%
“…When the Ehssp gene family was first identified, it was shown that some members of this gene family were responsive to heat and oxidative stresses (32). However, the authors did not determine how many members of the Ehssp gene family were responsive to stress, or if there were other members of the Ehssp gene family that were not stress responsive.…”
Section: Resultsmentioning
confidence: 99%